Host immunity to Mycobacterium tuberculosis and risk of tuberculosis: A longitudinal study among Greenlanders. Issue 48 (21st November 2016) - Michelsen, Sascha Wilk; Soborg, Bolette; Agger, Else Marie; Diaz, Lars Jorge; Hoff, Soren Tetens; Koch, Anders; Sorensen, Hans Christian Florian; Andersen, Peter; Wohlfahrt, Jan; Melbye, Mads
Highlights: Immunity to promising latent TB vaccine antigens did not reduce risk of TB. Immunity to latent TB antigens was observed among individuals categorised as not Mtb -infected. A large follow-up study with a clinical outcome in a setting with high TB transmission. Findings are not influenced by cross-reactions attributed to non tuberculous mycobacteria. Abstract: Background: Human immune responses to latent Mycobacterium tuberculosis ( Mtb ) infection (LTBI) may enable individuals to control Mtb infection and halt progression to tuberculosis (TB), a hypothesis applied in several novel TB vaccines. We aimed to evaluate whether immune responses to selected LTBI antigens were associated with subsequent reduced risk of progression to TB. Methods: We conducted a population-based cohort study in East Greenland (2012–2014) including individuals aged 5–31 years. A personal identifier allowed follow-up in national registers including the TB notification register. Mtb infection was defined by a positive Quantiferon test. Immune responses to LTBI antigens were assessed by whole blood antigen stimulation and interferon gamma measurement. Results: Among 978 participants, 67 previously had TB. LTBI antigen (Rv1284, Rv2659, Rv2660c) immune response prevalence was 18%, 50%, 2% among Mtb -infected and 7%, 40%, 4% among non-infected (Quantiferon negative) participants. Among 911 participants without prior notified TB, 31 were notified with TB during study follow-up. Immune responses to LTBI antigens were not associated with reduced risk of subsequent TB; Rv1284 HR 0.92 (95%CI 0.28–3.04), Rv2659 HR 1.05 (95%CI 0.51–2.13), Rv2660c HR 3.06 (95%CI 0.70–13.37). Conclusion: In this large population-based study, human immune responses to selected LTBI antigens were not found to be strongly associated with reduced risk of subsequent TB.